Effect of chronic ammonia nitrogen stress on the SOD activity and interferon-induced transmembrane protein 1 expression in the clam Cyclina sinensis - Ge, Hongxing; Ni, Qian; Liu, Jialing; Dong, Zhiguo; Chen, Shibo (Frontiers in Marine Science, 2022)
Ammonia nitrogen plays a crucial part in oxidative stress in aquatic animals. To elucidate the effect of ammonia nitrogen stress on the superoxide dismutase (SOD) activity and interferon-induced transmembrane protein 1 (IFITM1) expression in the clam Cyclina sinensis, clams were exposed to ammonia nitrogen (8.07 mg/L) for 768 h (32 days) and then challenged with Vibrio parahaemolyticus. The results showed that the SOD activity in the hepatopancreas of C. sinensis exposed to ammonia nitrogen first increased and then decreased with time, returning to the control group’s normal level at 768 h. Following infection with V. parahaemolyticus, the SOD activity in the hepatopancreas fluctuated over time. The SOD activity in clams infected with V. parahaemolyticus at 144 h did not return to the control group’s normal level. The full-length cDNA of CsIFITM1 was 2,434 bases in length, including a 2,301-bp open reading frame (ORF) encoding 714 amino acids, with a putative molecular weight of 83.86 kDa. CsIFITM1 contains an RNA helicase domain (DEXHc_RLR, DR) and a Helicase_C (HC) domain. The transcriptional levels of CsIFITM1 were upregulated by exposure to ammonia nitrogen and were significantly higher from 6 to 768 h compared to the control (0 h) (p < 0.05). Following infection with V. parahaemolyticus, the transcript levels of CsIFITM1 in the hepatopancreas were upregulated and were significantly higher from 6 to 144 h, in contrast to those of the control (0 h) (p < 0.05). The present data provide the first evidence of the SOD activity and CsIFITM1 transcript levels being able to reflect the effect of ammonia on the clam C. sinensis.